Mortality Risk in COVID-19 Patients with HIV-Comorbidity: Meta-Analysis - Nindita Arum Veibiani; Bhisma Murti; Argyo Demartoto (Journal of Epidemiology and Public Health, 2022)
Background: Coronavirus disease 2019 or known as COVID-19 is a disease caused by severe acute respiratory coronavirus 2 (SARS-CoV-2). Comorbidities that are risk factors for COVID-19 death include hypertension, diabetes, heart disease, COPD, HIV (Human Immunodeficiency Virus), kidney failure, and cancer. This study aims to estimate the magnitude of the risk of death in COVID-19 patients with comorbid HIV, with a meta-analysis of the primary studies conducted by the previous authors.Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, population: COVID-19 patients. Intervention: HIV comorbidity. Comparison: without co-morbid HIV. Outcome: Mortality. The articles used in this study were obtained from four databases, namely PubMed, Google Scholar, Springerlink, and Science direct, using the search keys "HIV/AIDS" AND "Mortality" OR "death" AND "COVID-19 OR SARS-CoV-2. The included article is a full-text English language with a cohort study design from 2020 to 2021 and reports the adjusted Odds Ratio (aOR) in a multivariate analysis. Article selection is done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 9 cohort studies involving 3,397,186 COVID-19 patients from America, Europe, and Africa were selected for a systematic review and meta-analysis. The data collected showed that COVID-19 patients with HIV comorbidities had a mortality risk of 3.30 times compared to COVID-19 patients without HIV comorbidities (aOR = 3.30; 95% CI = 2.87 to 3.81; p<0.001).Conclusion: HIV increases mortality risk in COVID-19 patients. Keywords: HIV, COVID-19, SARS-CoV-2, mortality Correspondence:Nindita Arum Veibiani. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: nindita.veibiani@gmail.com. Mobile: 085800216969.